2010
DOI: 10.1002/cphc.201000708
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Formation of Biocompatible Vesicles in Aqueous Mixtures of Amino Acid‐Based Cationic Surfactants and SDS/SDBS

Abstract: The spontaneous formation of vesicles by six amino acid-based cationic surfactants and two anionic surfactants (sodium dodecylbenzene sulfonate (SDBS) and sodium dodecyl sulfate (SDS)) is reported. The head-group structure of the cationic surfactants is minutely altered to understand their effect on vesicle formation. To establish the regulatory role of the aromatic group in self-aggregation, both aliphatic and aromatic side-chain-substituted amino acid-based cationic surfactants are used. The presence of arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…We found that with increasing amount of SDS (0–10 mM) in 2 mM CTAB solution, the KE catalytic activity is reduced. Indeed, in the presence of 2 mM CTAB and 10 mM SDS, the solution contains vesicles of diameters 150±30 nm (checked by DLS and TEM, comparable to reported literature; [40–42] Figures S15b and S17) and possess no KE catalytic activity (Figure S10). However, addition of cyt c enhanced KE catalytic activity by almost 250‐fold.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…We found that with increasing amount of SDS (0–10 mM) in 2 mM CTAB solution, the KE catalytic activity is reduced. Indeed, in the presence of 2 mM CTAB and 10 mM SDS, the solution contains vesicles of diameters 150±30 nm (checked by DLS and TEM, comparable to reported literature; [40–42] Figures S15b and S17) and possess no KE catalytic activity (Figure S10). However, addition of cyt c enhanced KE catalytic activity by almost 250‐fold.…”
Section: Resultssupporting
confidence: 85%
“…After observing that cyt c can show superior KE catalysis, we were interested to study this phenomenon in bilayer membrane containing vesicular system. As before, we first measured the non‐specific catalytic activity of the catanionic vesicle composed of CTAB and SDS [40–42] . We found that with increasing amount of SDS (0–10 mM) in 2 mM CTAB solution, the KE catalytic activity is reduced.…”
Section: Resultsmentioning
confidence: 97%
“…In this regard, Shome et al reported the formation of bilayered vesicles by mixing amino acid-functionalized cationic surfactants (3a−c) with anionic surfactants such as sodium dodecylbenzenesulfonate (SDBS) and sodium dodecyl sulfate (SDS)). 43 Vesicular self-association was mainly guided by the HLB of both cationic and anionic surfactants. Considering the cargo-carrying ability of the vesicles, we tested its cytocompatibility, one of the prerequisites of a delivery vehicle.…”
Section: ■ Supramolecular Self-assemblies: Insight and Design Principlesmentioning
confidence: 99%
“…Typically, the source of spontaneous bilayer curvature includes compositional asymmetry, which stabilizes equal and opposite spontaneous monolayer curvatures, such as that obtained by mixing two different amphiphilic molecules. [1,21,24,[26][27][28] Symmetric (or monocomponent) bilayers have zero spontaneous curvature. Justifying the reason for vesiculation is more difficult.…”
Section: Introductionmentioning
confidence: 99%